Comparative study of multiple sclerosis patients based on distance from the advanced health center - Tosun, Hatice; Tecellioglu, Mehmet (Annals of Medical Research, 2021)
Aim: There are several reasons for presenting to a hospital for multiple sclerosis (MS), a neurodegenerative disorder. We aimed to determine how distance affects presentation by patients with MS to an advanced health center in Malatya, Turkey. Materials and Methods: The study was performed on 109 patients at the Neurology Department of Inonu University Hospital in 2017. The patients were divided into group-1, who lived in Malatya, and group-2, who live in the upstate region. Demographic and clinical data were analyzed retrospectively from medical records. Chi-square tests, independent sample T-tests, and Mann–Whitney U-tests were used to analyze the data. Results: The duration of the disease was longer among patients who lived in Malatya. In terms of mean expanded disability status scale scores, patients who lived in Malatya had higher scores and patients who lived upstate exhibited more clinical complaints. Among patients who lived upstate, there were more motor problems, vertigo, cognitive impairment, psychiatric disturbances, and visits for blood tests. Conclusion: Distance affected admission to MS outpatient clinics. We should be more careful in terms of attack when assessing the reasons of patients present from outside the province. More meaningful results can be obtained by following more patients for longer periods.